MODEL OF MSME PERFORMANCE BASED ON BUSINESS DIGITALIZATION, HUMAN RESOURCES, CAPITAL AND CRM COMPETENCE - Bahtiar Efendi (Jurnal Ekonomi, 2023)
The biggest challenge in facing this new era is how businesses must start over with capital that can be said to be minus the results of business operations that had died during the Covid-19 outbreak. Important points that must be considered to face the new normal phase in business are crisis management, labor, supply chain, tax and trade finance and liquidity, as well as strategy and brand. This study aims to examine the effect of business digitalization, human resources, capital and customer relationship marketing (CRM) competencies on the performance of wedding souvenir craft MSMEs in the New Normal Era. This research includes quantitative research with a survey approach. The population in this study were employees in MSMEs crafting wedding souvenirs in Banjarnegara Regency totaling 42 people spread across 5 MSMEs. The results concluded that both partially and jointly there was a positive and significant effect of business digitalization, human resources, capital and CRM competencies together on the performance of Wedding Souvenir Craft MSMEs in Banjarnegara Regency in the New Normal Era. The variable that has the dominant effect is CRM competence.